The extent Of Acquiring the Skills of Mathematical Thinking Based on International Trends in Math and Science Study TIMSS among Bani kinana’s 8th grade Students - Kanaan, Mustafa Mohamed Hadi (Journal of Educational and Psychological Sciences, 2020)
This study aims at investigating the extent of acquiring the mathematical thinking skills for 8th Grade students. The study will also investigate if the impact of the type of skill and gender on the students’ level of achievement. For this purpose, the descriptive analytical framework was utilized. This was carried on by applying a test consisting of 21 elements distributed on the seven mathematical thinking skills (expression by symbols، generalization، induction، deduction، logical thinking، modelling، and mathematical proof). The sample will be 620 8th Grade male and female students. The results reveal that there is a weakness of achievement among 8th Grade students on the level of mathematical thinking skills، and this weakness is not limited to male students but can be noticed among female ones. According to these results، the study finds it better to hold training programs based on the recommendations of International Mathematical Study TIMSS.